Synthesis, Characterization and Preliminary Anticancer Study of Novel 5-fluorouracil Conjugate with Pyrrolidine Dithiocarbamate as a Mutual Anticancer Prodrug - Shihab, Ikram K.; H. Mohammed, Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2019)
5-Fluorouracil is one of the commonly used chemotherapy drugs in anticancer therapy; unfortunately treatment with 5-FU by solely has many drawbacks low lipophilicity, low permeability, low molecular weight, and its relatively poor plasma protein binding; also a brief half-life therefore frequent administration is required to maintain the optimal therapeutic plasma level which in addition to its poor selectivity, drug resistance and limited penetration to cancer cells; leads to increased incidence of side-effects to healthy cells/tissues and low response rates. In order to minimize these drawbacks; 5-FU was chemically conjugated with pyrrolidine dithiocarbamate (PDTC) in a mutual prodrug moiety (S-(9H-purin-6-yl) 3-((pyrrolidine-1-carbonothioyl)thio)propanethioate) "compound [IV]" with (chloroacetic acid) and (chloroethanol) being the linkers ;synthesized prodrug and intermediates were characterized and identified using FTIR ,1H NMR and all the results shown good agreements with the proposed chemical structures of the synthesized compounds. ; in-vitro preliminary cytotoxicity study was conducted for compound [IV] and 5-FU on CAL 51 and B16V cell lines ,results showed enhanced cytotoxic effects for [IV] over 5-FU.